Engineering viroid resistance - Dalakouras, Athanasios; Dadami, Elena; Wassenegger, Michael (Viruses, 2015)
Viroids are non-encapsidated, non-coding, circular, single-stranded RNAs (ssRNAs). They are classified into the families Pospiviroidae and Avsunviroidae, whose members replicate in the nucleus and chloroplast of plant cells, respectively. Viroids have a wide host range, including crop and ornamental plants, and can cause devastating diseases with significant economic losses. Thus, several viroids are world-wide, classified as quarantine pathogens and, hence, there is an urgent need for the development of robust antiviroid strategies. RNA silencing-based technologies seem to be a promising tool in this direction. Here, we review the recent advances concerning the complex interaction of viroids with the host’s RNA silencing machinery, evaluate past and present antiviroid approaches, and finally suggest alternative strategies that could potentially be employed in the future in order to achieve transgenic and non-transgenic viroid-free plants.
Gesehen am 16.12.2020